STRES IBU DALAM MENGASUH ANAK PADA KELUARGA DENGAN ANAK PERTAMA BERUSIA DI BAWAH DUA TAHUN - Sari, Dian Yunita; Krisnatuti, Diah; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
Parenting practice is often become a source of stress for parents, especially for family who still has young children. The aim of this research was to analyze the influence of family characteristic, source of stress, allocation of parenting time, family expenses for children, social support, and home appliances on mother’s stress. The design of the research was cross sectional study and involved 120 mothers who had first children under two years old (60 working mothers and 60 nonworking mothers). The sample selected by purposive sampling; the studysites were Ratujaya and Bojong Pondok Terong Village, Depok City, West Java Province. The analysis data use correlation and multiple linear regresion tests. The study revealed that mother’s parenting stress had negative significant correlation with father’s education, mother’s education, and family expenses for children; but had positive significant correlation with source of stress. The multiple linear regression found that mother’s stress was influenced by father’s education, source of stress, and family expenses for children. Source of stress that was caused by the presence of children influenced significantly increasing of mother’s stress. On the contrary, increasing of father’s education and increasing of family expenses for children caused significantly decreasing of stress among mothers in family with first children under two years old.